Enhancing athletic gymnastics training through the use of artificial intelligence - Shcherbin D. V.; Tretyakov A. A.; Putilina V. Yu.; Shilova M. V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to assess the efficacy of AI-powered programs in amateur athletic gymnastics training.